Electric and Thermal Properties of Wet Cable 10kV and 15kV - K. Rajagopala (Indonesian Journal of Electrical Engineering and Computer Science, 2012)
The increased temperature of the cable insulation with rising load currents, are known to accelerate the formation of water and electric trees in cables which ultimately lead to cables failure. There are several factors which will determine the thermal and electrical behaviour of a given wet cable installation. These include the assumed ampacity, the cable construction and circumstances of installation, the thermal properties of the surrounding soil and the electrical properties. The work presented in this paper involves the use of COMSOL multiphysics finite element software to develop an integrated electrical, thermal model with 5micro meter and 2.5 micro meter water bubble radius. The presence of water tree results in the reduction of their dielectric strength. Here the finite element simulation technique is used to evaluate the electric field, potential and temperature distribution inside the 10 kV and 15 kV power cables. A model that illustrates the water-dielectric interface within the cable insulation system is proposed.DOI: http://dx.doi.org/10.11591/telkomnika.v10i7.1298